The Chemical Reactor from Laboratory to Industrial Plant A Modern Approach to Chemical Reaction Engineering with Different Case Histories and Exercises - Santacesaria, Elio; Tesser, Riccardo (Springer International Publishing : Imprint: Springer, 2018)
This graduate textbook, written by a former lecturer, addresses industrial chemical reaction topics, focusing on the commercial-scale exploitation of chemical reactions. It introduces students to the concepts behind the successful design and operation of chemical reactors, with an emphasis on qualitative arguments, simple design methods, graphical procedures, and frequent comparison of capabilities of the major reactor types. It starts by discussing simple ideas before moving on to more advanced concepts with the support of numerous case studies. Many simple and advanced exercises are present in each chapter and the detailed MATLAB code for their solution is available to the reader as supplementary material on Springer website. It is written for MSc chemical engineering students and novice researchers working in industrial laboratories.